Comparison between two generations to verify the morphological changes in female futsal athletes in a period of 10 years - Marcos Roberto Queiroga; Sandra Aires Ferreira; Timothy Gustavo Cavazzotto; Bruno Sergio Portela; Marcus Peikriszwili Tartaruga; Matheus Amarante do Nascimento; Danilo Fernandes da Silva (Universidade Federal de Santa Catarina, 2019)
The aim was to compare two generations to verify the morphological changes in female futsal athletes. Age, years of playing, anthropometry measurements, percentage body fat and somatotype were compared between professional athletes in 2001 (n=112) and 2011 (n=115). The 2011 group revealed a significant longer practice time (9.0±4.3 vs. 5.7±3.5 years; p<0.001), higher thigh skinfold (26.1±8.5 vs. 22.5±6.7 mm; p<0.001), circumference of tensed forearm (27.4±2.1 vs. 26.7±2.1 cm; p=0.007), mesomorphy (4.1 vs. 3.3; p=0.001) and lower supraspinale skinfold (14.0±5.0 vs. 19.1±7.4 mm; p<0.001), trunk/extremity relationship (0.8±0.3 vs. 1.1±0.1; p<0.001) and endomorphy (4.5 vs. 5.0; p=0.009) than those of the 2001 athletes. Comparison in playing positions revealed that the 2011 goalkeepers (9.5±5.0 vs. 6.3±3.4 years; p=0.027), wings (9.0±4.3 vs. 5.4±3.2 years; p=0.001) and fixed (8.4±4.3 vs. 6.9±4.5 years; p=0.001) practiced more time than the 2001 athletes, whereas the somatotype profile of goalkeepers (4.6±1.0 vs. 3.4±1.1; p=0.001), wings (3.9±0.8 vs. 3.0±0.9; p=0.001), pivots (3.8±1.0 vs. 3.4±1.0; p=0.028) and fixed (4.3±0.9 vs. 3.7±1.0; p=0.036) registered a higher mesomorphy rate than that of the 2001 athletes, respectively. We may conclude that the 2011 group showed a significant increase in practicing time, coupled to higher mesomorphy and lower endomorphy rates than those experienced by the 2001 athletes.